(untitled) (Confluenţe Bibliologice, 2013)
The article explores the sacred role of the teacher in the moral-spiritual formation of believers, drawing inspiration from the evangelical teachings and the writings of the Holy Fathers. The author emphasizes the importance of personal example, deep knowledge of Scripture and love for God as the foundations of true teaching service. The text is an exhortation to live faith through deeds and to cultivate Christian virtues through education.